2015
DOI: 10.1371/journal.pone.0123459
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone as Adjuvant to Bupivacaine Prolongs the Duration of Thermal Antinociception and Prevents Bupivacaine-Induced Rebound Hyperalgesia via Regional Mechanism in a Mouse Sciatic Nerve Block Model

Abstract: BackgroundDexamethasone has been studied as an effective adjuvant to prolong the analgesia duration of local anesthetics in peripheral nerve block. However, the route of action for dexamethasone and its potential neurotoxicity are still unclear.MethodsA mouse sciatic nerve block model was used. The sciatic nerve was injected with 60ul of combinations of various medications, including dexamethasone and/or bupivacaine. Neurobehavioral changes were observed for 2 days prior to injection, and then continuously for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 40 publications
(40 reference statements)
2
62
0
1
Order By: Relevance
“…Recent studies do not support any evidence of neural toxicity of dexamethasone when administered perineurally. 26,27 However, these experimental results need to be confirmed before extending the routine use of perineural administration to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies do not support any evidence of neural toxicity of dexamethasone when administered perineurally. 26,27 However, these experimental results need to be confirmed before extending the routine use of perineural administration to humans.…”
Section: Discussionmentioning
confidence: 99%
“…The use of additional adjuvants were approbated in clinical practice with the aim of prolonging the duration of the single shot PNB, for example, clonidine [50], opioids [51], midazolam [52], ketamine [53] with little effect. DXM was evaluated and appear to be an effective agent for prolonging the duration of PNB in preclinical [23,24], and clinical investigations [13-19, 25, 26]. Most of the previous studies were focused on clarifying the effects of DXM as a local anesthetic adjuvant for brachial plexus block [14,16], but even after a systemic review and meta-analysis the authors concluded that "Perineural administration of dexamethasone with LA prolongs brachial plexus block effects with no observed adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…The scattered experimental data do not enable their combination into an integral theory explaining this phenomenon [20][21][22][23][24]. The systemic anti-inflammatory action of DXM is well known, and this agent is recommended as a drug commonly used in multimodal pain control methods in knee arthroplasty [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, un metanálisis reciente encontró que la administración de dexametasona perineural aumenta la duración del bloqueo en comparación con la administración intravenosa, con un efecto de ahorro de opioides pequeño pero significativo (7,1 mg de equivalentes de morfina oral [intervalo de confianza del 95 %, 0,74-13,5 mg]) a las 24 horas (66). Aunque siguen existiendo preocupaciones teóricas con respecto al potencial de la neurotoxicidad con dexametasona, estudios recientes in vivo en animales a dosis clínicamente relevantes no respaldan esta hipótesis y, de hecho, demuestran un posible efecto neuroprotector (67,68).…”
Section: Dexametasonaunclassified